Improved gross motor skills of children aged 4- 6 years through shuttle run games and throwing bounce balls - Atiq, Ahmad; Evasari, yona; Yafdas, Yoas; Womsiwor, Frans (Universitas Nusantara PGRI Kediri, 2021)
Motor skills in children are a skill that every child must master. Having less than optimal gross motor activity makes children can interfere with activities in children. So it requires a solution to improve gross motor skills in order to develop optimally. This study aimed to find out the effectiveness of motor improvement in children aged 4-6 years. The research method used is Classroom Action Research, with data collection in this study using performance, observation, interviews, and documentation. The subjects of this study used a saturated sampling technique of 45 children of Mujahideen Kindergarten 2 Pontianak. Data analysis compares the results obtained from cycle I and cycle II with descriptive quantitative approaches. The results of this study showed an increase in children's gross motor skills through shuttle run games, and ball bounce throwing, evidenced by the number of students who increased their motor skills from 45 students from the first cycle of 16% or 16 students classified as good motor and in cycle II increased from 45 students 71% or 32 students fall into the category of good. Shuttle run and ball bounce throw are solutions to improve gross motor skills in children aged 4-6 years.